PENGARUH PENGGUNAAN MEDIA E-BOOKLET TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2023)
Abstract: This study aims to determine the effect of using e-booklet media on student learning outcomes in theme 6 sub-theme 2 class III SD Negeri 104201 Kolam T.A 2022/2023. This type of research uses a quasi-experimental method. Data was collected using multiple choice instruments. The data analysis technique was a two-sample T-test assisted by the SPSS 22 application. The results of the study using a two-sample T-test obtained a significant value (2 tailed) 0.000